2011
DOI: 10.1007/s10911-011-9222-4
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and Associated Signaling Pathways that Control Normal Breast Epithelium and Breast Cancer

Abstract: This review article discusses recent work on the melatonin-mediated circadian regulation and integration of molecular and metabolic signaling mechanisms involved in human breast cancer growth and the associated consequences of circadian disruption by exposure to light-at-night (LAN). The anti-proliferative effects of the circadian melatonin signal are, in general, mediated through mechanisms involving the activation of MT(1) melatonin receptors expressed in human breast cancer cell lines and xenografts. In est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 59 publications
4
82
0
1
Order By: Relevance
“…The repression of the nocturnal circadian melatonin signal promotes tumor aerobic glycolysis and the expression and activation of the signaling pathways involved in tumor proliferation and survival that drive resistance in cancer cells to endocrine therapies and chemotherapies [40]. Therefore, the melatonin signal regulates metabolic and cell signaling activities to inhibit cancer initiation, promotion, and progression [162], and these effects can be mediated by melatonin MT 1 /MT 2 receptors [163].…”
Section: Circadian Disruptionmentioning
confidence: 99%
“…The repression of the nocturnal circadian melatonin signal promotes tumor aerobic glycolysis and the expression and activation of the signaling pathways involved in tumor proliferation and survival that drive resistance in cancer cells to endocrine therapies and chemotherapies [40]. Therefore, the melatonin signal regulates metabolic and cell signaling activities to inhibit cancer initiation, promotion, and progression [162], and these effects can be mediated by melatonin MT 1 /MT 2 receptors [163].…”
Section: Circadian Disruptionmentioning
confidence: 99%
“…Moreover, preclinical in vitro and in vivo studies and clinical trials showed that melatonin was able to exert an oncostatic action on different tumors (Girgert et al, 2009;Hill et al, 2009Hill et al, , 2011aJung and Ahmad, 2006;Sánchez-Barceló et al, 2012;Srinivasan et al, 2008), to increase the efficacy of chemotherapy when used in adjuvant settings and to decrease the side effects (Vijayalaxmi et al, 2002). Since proliferation and differentiation are typical of any cell system and are carefully regulated in the course of physiological development and life cycle, tumor evolution must imply a deregulation of their morphofunctional features.…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed a positive correlation between age and serum 25OHD levels for both the males and females. Age was shown to be positively associated with 25OHD levels in previous reports [15,55]. Lower serum 25OHD levels in younger individuals has been suggested to be associated with their lower forearm bone mineral content [15].…”
Section: Vitamin D Deficiency and Night Shift Work O R I G I N A L P mentioning
confidence: 86%
“…A number of factors have been found to be associated with low 25OHD levels. These factors include, among others, low sun exposure, age, obesity, smoking, dress style in the case of women and physical activity [5,[13][14][15][16][17][18][19][20]. In the absence of adequate sun exposure, 25OHD levels may be insufficient to achieve the desired physiologic role [5,[21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%